Peningkatan Daya Saing UMKM Geresik melalui Sertifikasi Halal - Kiswara Rahmantya, Yanneri Elfa; Djuniardi, Dede; Maulana, Ahmad Syahid Ridlo (Penerbit Widina, Widina Media Utama, 2024)
The Community Service Program (PKM) is a form of contribution by higher education institutions to support the development and empowerment of the community, particularly in the economic sector. Through this initiative, universities aim to provide practical solutions to the problems faced by the community, including enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). The community service program in Geresik Village, Ciawigebang District, Kuningan Regency aims to enhance the competitiveness of MSMEs through halal certification. This program involves intensive training on the importance of halal certification, the registration process, and relevant regulations. The methods employed in this PKM activity include workshops, hands-on training sessions, and one-on-one consultations to address specific concerns of MSMEs. Key stakeholders involved in this program include university faculty members, local government officials, representatives from halal certification bodies, and MSME owners from the village. The results show an increase in the capacity and knowledge of MSME actors; however, there are challenges in separating raw materials and prioritizing products that need certification. The main issues faced include a lack of awareness about the added value of products with halal certification and the costs associated with obtaining the certificate. This program emphasizes the need for continuous education and financial support to ensure that MSMEs can leverage halal certification to improve product competitiveness. Collaboration with the government, community, and private sector is crucial to achieving this goal.ABSTRAKProgram Pengabdian kepada Masyarakat (PKM) merupakan salah satu bentuk kontribusi perguruan tinggi dalam mendukung pengembangan dan pemberdayaan masyarakat, terutama di sektor ekonomi. Melalui kegiatan ini, universitas berupaya untuk memberikan solusi nyata atas permasalahan yang dihadapi oleh masyarakat, termasuk dalam hal peningkatan daya saing Usaha Mikro, Kecil, dan Menengah (UMKM). Program pengabdian masyarakat di Desa Geresik, Kecamatan Ciawigebang, Kabupaten Kuningan bertujuan meningkatkan daya saing UMKM melalui sertifikasi halal. Kegiatan ini melibatkan pelatihan intensif tentang pentingnya sertifikasi halal, proses pendaftaran, dan regulasi yang relevan. Metode yang digunakan dalam kegiatan PKM ini meliputi lokakarya, sesi pelatihan langsung, dan konsultasi satu per satu untuk mengatasi masalah spesifik yang dihadapi oleh UMKM. Para pemangku kepentingan yang terlibat dalam program ini mencakup dosen universitas, pejabat pemerintah daerah, perwakilan dari badan sertifikasi halal, dan pemilik UMKM dari desa tersebut. Hasilnya menunjukkan peningkatan kapasitas dan pengetahuan pelaku UMKM; namun, terdapat kendala dalam pemisahan bahan baku dan prioritas produk yang perlu disertifikasi. Masalah utama yang dihadapi adalah kurangnya kesadaran tentang peningkatan nilai produk dengan sertifikasi halal dan biaya pengurusan sertifikat. Program ini menekankan perlunya edukasi berkelanjutan dan dukungan finansial untuk memastikan UMKM dapat memanfaatkan sertifikasi halal demi meningkatkan daya saing produk. Kolaborasi dengan pemerintah, masyarakat, dan sektor swasta sangat penting untuk mencapai tujuan ini.